2012
DOI: 10.4049/jimmunol.1102422
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Selectively Preserve Immune Privilege of Self-Antigens during Viral Central Nervous System Infection

Abstract: Regulatory T cells (Tregs) are important for the attenuation of immune reactions. During viral CNS infections, however, an indiscriminate maintenance of CNS immune privilege through Treg-mediated negative regulation could prevent autoimmune sequelae but impair the control of viral replication. We analyzed in this study the impact of Tregs on the development of acute viral encephalomyelitis, T cell-mediated antiviral protection, and prevention of CNS autoimmunity following intranasal infection with the gliatrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 46 publications
3
36
0
Order By: Relevance
“…It also not excluded that IP-10 production subsequent to the early peak of IFN-I is fueled by other factors, such as IFN-γ or TNF-α [41]. IP-10 is the ligand of CXCR3, which is expressed on many cells (activated T cells, Th1 cells, Treg cells, plasmacytoid dendritic cells, monocytes, NK cells) and is implicated in the recruitment of CXCR3 + cells to lymph nodes [42], [43], [44]. Events in lymph nodes might have a particular impact on immunodeficiency [45].…”
Section: Discussionmentioning
confidence: 99%
“…It also not excluded that IP-10 production subsequent to the early peak of IFN-I is fueled by other factors, such as IFN-γ or TNF-α [41]. IP-10 is the ligand of CXCR3, which is expressed on many cells (activated T cells, Th1 cells, Treg cells, plasmacytoid dendritic cells, monocytes, NK cells) and is implicated in the recruitment of CXCR3 + cells to lymph nodes [42], [43], [44]. Events in lymph nodes might have a particular impact on immunodeficiency [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, peripheral MHV infection correlated with induction of SR T cells detected within the spleen of chronically infected mice (Kyuwa et al, 1991). More recently, it was demonstrated that acute MHV-A59 infection supports peripheral proliferation and CNS recruitment of transferred T-cell receptor transgenic myelin-specific CD4 T cells (Cervantes-Barragan et al, 2012). Similarly, we showed that naïve myelin oligodendrocyte glycoprotein (MOG)-specific CD4 T cells transferred prior to JHMV infection proliferated in cervical lymph nodes (CLN) and migrate to the CNS (Savarin et al, 2015).…”
Section: Self Reactive Cd4 T Cell Response During Neurotropic Mhv mentioning
confidence: 99%
“…This concept is well-illustrated by the demyelinating disease that develops following infection with a neurotropic strain of murine hepatitis virus (MHV). Depletion of Treg cells in this context has little or no effect on the magnitude of the anti-viral immune response or viral clearance, but greatly exacerbates neurological pathology and the activation of myelin-specific T cells (142), indicating that at least in this case Treg cells are selectively modulating the activation and functional differentiation of self-reactive T cells.…”
Section: Critical Issues In Treg Cell Biologymentioning
confidence: 99%